Evaluating and ranking the Vulnerability of the marine ecosystem to multiple threats - SEA K., GREEN; M., RAJAKUMAR; T., UMAMAHESWARI; N. V., SUJATH KUMAR; P., JAWAHAR; KEER, NARESH RAJ; YADAV, RAJPAL; yadav, AJAY Kumar (The Indian Journal of Animal Sciences, 2022)
Marine ecosystem is threatened by a suite of climatic, anthropogenic, agricultural and aquacultural and fishing stressors. Agriculture and anthropogenic activity are the major drivers of biodiversity loss by extensive use of pesticides and fertilizers, and encounter depleted soils and erosion due to unsustainable farming practices. This study provides an assessment of the various potential threats that vulnerability of marine biodiversity in the Gulf of Mannar. In order to collect the data, a questionnaire was distributed to more than 100 resource users from four districts of GOMBRT in binary format. The data was then explored using multivariate logit regression method followed by Hosmer-Lemeshow test. The evaluation showed that all the determinants of various threats significantly affect the vulnerability of marine ecosystem. Among the studied factors, change in sea temperature, increase in fishing efforts, advanced farming practices, occurrence of endangered species, and tourism were greatest threats (high log odds ratio), identified as most important determinants affecting marine ecosystem.Marine ecosystem is threatened by a suite of climatic, anthropogenic, agricultural and aquacultural and fishing stressors. Agriculture and anthropogenic activity are the major drivers of biodiversity loss by extensive use of pesticides and fertilizers, and encounter depleted soils and erosion due to unsustainable farming practices. This study provides an assessment of the various potential threats that vulnerability of marine biodiversity in the Gulf of Mannar. In order to collect the data, a questionnaire was distributed to more than 100 resource users from four districts of GOMBRT in binary format. The data was then explored using multivariate logit regression method followed by Hosmer-Lemeshow test. The evaluation showed that all the determinants of various threats significantly affect the vulnerability of marine ecosystem. Among the studied factors, change in sea temperature, increase in fishing efforts, advanced farming practices, occurrence of endangered species, and tourism were greatest threats (high log odds ratio), identified as most important determinants affecting marine ecosystem.